Undergraduate Students' Intelligence Profiles According to the Tes Intelligensi Kolektif Indonesia Tinggi (TIKI-T): A Cluster Analysis Based on the Rasch Model Person Ability - Yudiana, Whisnu; Susanto, Hery; Triwahyuni, Airin (Makara Human Behavior Studies in Asia, 2019)
This research aims to identify undergraduate students’ intelligence profiles using a two-stage cluster analysis based on the person’s ability of the Rasch model to examine the effect of the clusters on academic performance. A total of 1443 undergraduate students from nine academic disciplines at Universitas Padjadjaran in Bandung, Indonesia, participated in the study, completing 11 subtests of the Tes Intelligensi Kolektip Indonesia Tinggi (TIKI-T). A hierarchical cluster analysis approach using Ward’s linkage method and squared Euclidean distance was conducted, followed by a nonhierarchical k-means cluster analysis using simple Euclidean distance as the similarity measure to examine two-, three-, four-, and five-cluster solutions. An intra-class correlation (ICC) and a discriminant analysis were also conducted to validate the cluster membership results. This research identified five profiles of intelligence that had an effect on academic performance. Students with high scores in the scholastic aptitude subtests tended to have higher grade point average than those with high scores in the nonverbal ability subtests and the speed and accuracy ability subtests. The findings can be used as a recommendation for psychologists in Indonesia for university placement tests.